1997
DOI: 10.1152/ajpheart.1997.273.6.h2627
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity exercise training decreases cardiac output and hypertension in spontaneously hypertensive rats

Abstract: The decrease in cardiac sympathetic tone and heart rate after low-intensity exercise training may have hemodynamic consequences in spontaneously hypertensive rats (SHR). The effects of exercise training of low and high intensity on resting blood pressure, cardiac output, and total peripheral resistance were studied in sedentary ( n = 17), low- ( n = 17), and high-intensity exercise-trained ( n = 17) SHR. Exercise training was performed on a treadmill for 60 min, 5 times per week for 18 weeks, at 55% or 85% max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
3
30

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 21 publications
13
126
3
30
Order By: Relevance
“…Aerobic training is currently recommended as a potent coadjuvant of the pharmacological treatment of hypertension, mainly because it attenuates (but does not normalize) resting blood pressure in hypertensive animals (2,22,23,25,(34)(35)(36)(37)(38)(39) and humans (40,41).…”
Section: Mechanisms Conditioning Training-induced Hemodynamic Changesmentioning
confidence: 99%
“…Aerobic training is currently recommended as a potent coadjuvant of the pharmacological treatment of hypertension, mainly because it attenuates (but does not normalize) resting blood pressure in hypertensive animals (2,22,23,25,(34)(35)(36)(37)(38)(39) and humans (40,41).…”
Section: Mechanisms Conditioning Training-induced Hemodynamic Changesmentioning
confidence: 99%
“…[5][6][7] Favourable modifications in autonomic modulation and BP have been documented following endurance training in animals and humans. [8][9][10][11][12] Our prior study has demonstrated an augmentation in parasympathetic or vagal modulation and enhanced baroreflex sensitivity (BRS) and arterial compliance (AC) following aerobic training. [13][14][15][16][17][18][19][20][21] Not surprisingly, few of these studies assessed these effects in African-American men, not in populations other than whites.…”
Section: Introductionmentioning
confidence: 99%
“…The heart rate seems to be reduced by low-intensity exercise training in SHR, likely due to a decrease in the sympathetic tone to the heart (17). This effect has been also attributed to causing the decrease in the cardiac output in low-intensity exercise-trained SHR and, consequently, for reducing the hypertension (46). Postexercise hypotension may persist for more than 12 h (16,19), and it has been reported that arterial baroreceptor reflex is required for this reduction in arterial pressure (7), but all of the mechanisms underlying this effect are not fully understood.…”
mentioning
confidence: 97%